Pengaruh Perilaku Adaptif dan Budaya Organisasi Pada Perusahaan Keluarga Terhadap Kepuasan Kerja Karyawan Melalui Suksesi Kepemimpinan Sebagai Variabel Intervening - Muhammad Hidayat; Mukhtar Galib (AkMen JURNAL ILMIAH, 2022)
The purpose of this study was to determine the effect of adaptive behavior and organizational culture on work satisfaction through leadership succession. The research data was generated by distributing questionnaires to 70 employees who were selected purposively as samples in this study. All research data were analyzed through smart PLS with two stages of analysis, namely algorithm analysis and boostraping analysis to determine the quality of research data and test research hypotheses. The results of this study show that adaptive behavior has a direct effect on work satisfaction, organizational culture has a direct effect on work satisfaction, adaptive behavior affects leadership succession, organizational culture affects leadership succession, leadership succession affects performance, analysis of indirect effects shows that adaptive behavior affects work satisfaction. through leadership succession and organizational culture affect work satisfaction through leadership succession